2018
DOI: 10.3390/w10040513
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Hydrological Simulation of CMADS and CFSR Reanalysis Datasets in the Qinghai-Tibet Plateau

Abstract: Multisource reanalysis datasets provide an effective way to help us understand hydrological processes in inland alpine regions with sparsely distributed weather stations. The accuracy and quality of two widely used datasets, the China Meteorological Assimilation Driving Datasets to force the SWAT model (CMADS), and the Climate Forecast System Reanalysis (CFSR) in the Qinghai-Tibet Plateau (TP), were evaluated in this paper. The accuracy of daily precipitation, max/min temperature, relative humidity and wind sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
87
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(90 citation statements)
references
References 48 publications
3
87
0
Order By: Relevance
“…It covers the entire East Asian region [14]. Some studies considered that CMADS+SWAT have better results for runoff simulation [15,16]. Meng et al [17] evaluated the water cycle in an area without meteorological data using the CMADS meteorological data.…”
Section: Introductionmentioning
confidence: 99%
“…It covers the entire East Asian region [14]. Some studies considered that CMADS+SWAT have better results for runoff simulation [15,16]. Meng et al [17] evaluated the water cycle in an area without meteorological data using the CMADS meteorological data.…”
Section: Introductionmentioning
confidence: 99%
“…In order to better reflect the spatial distribution of precipitation, the China Meteorological Assimilation Driving Datasets for the SWAT model version 1.0 (CMADS V1.0) was introduced in this study [50]. The CMADS was developed by Dr. Xianyong Meng from the China Institute of Water Resources and Hydropower Research (IWHR) and has received worldwide attention [28][29][30]. In the CMADS, the integration of air temperature, air pressure, humidity, and wind velocity data were mainly achieved through the LAPS (Local Analysis and Prediction System)/STMAS (Space-Time Multiscale Analysis System).…”
Section: Data Collectionmentioning
confidence: 99%
“…Based on this method, several products have been developed and widely applied in hydrological modeling [26,27]. The China Meteorological Assimilation Driving Datasets for the SWAT model (CMADS), which was developed by Dr. Xianyong Meng from the China Institute of Water Resources and Hydropower Research (IWHR), is one such product and has been widely applied in numerous studies [28][29][30][31]. For example, Liu [28] found that CMADS had unique advantages in hydrological simulations compared with observed data and Climate Forecast System Reanalysis (CFSR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, the distribution of soil moisture in sloping black soil farmland during freeze-thaw cycles in Northeastern China is discussed. Soil moisture has great impacts on food security, human CMADS has been used successfully in different basins, such as the Heihe River Basin, Juntanghu Basin, Manas River Basin, and Han River Basin, indicating good applicability of CMADS in East Asia [38][39][40][41][42][43][44][45][46][47][48][49][50]. However, the relative studies mainly focused on the surface hydrological process and meteorological data, whereas the application of the CMADS-ST to soil temperature and soil moisture distribution has been rarely studied, especially in the black soil zone [51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%